Approaches to minimize tooth staining associated with silver diamine fluoride: A systematic review. Issue 2 (11th January 2023) - Asghar, Mehmood; Omar, Ros Anita; Yahya, Rosiyah; Yap, Adrian Ujin; Shaikh, Muhammad Saad
Abstract: Objective: To the effectiveness of different strategies to overcome silver diamine fluoride (SDF)‐mediated tooth staining. Materials and Methods: Four online databases (PubMed, ScienceDirect, Scopus, and Web of Science) were searched using different MeSH terms and Boolean Operators to retrieve the articles (until June 2021), followed by a hand‐search of the reference list of the included articles. All full‐text, original studies in English that evaluated SDF staining and at least one SDF modification/alternative were included. Results: Among the assessed studies, nine studies explored the stain‐minimization effect of potassium iodide (KI) post‐application following SDF treatment. Among these, eight concluded that KI application after SDF treatment significantly reduced tooth staining, while one showed marginal staining following glass ionomer restoration of the SDF‐treated dentine. Additionally, one study applied potassium fluoride (KF) and silver nitrate (AgNO3 ) concurrently to mitigate SDF‐mediated staining. One study compared SDF staining with polyethylene glycol (PEG)‐coated nanoparticles containing sodium fluoride (NaF), and another used nanosilver fluoride (NSF) for staining comparison with SDF. Conclusions: Within the limitations of this study, the addition of different materials to SDF has proven to be a beneficial strategy for overcoming tooth staining associated with SDF. Future studies are warranted, particularly clinical trials, to validate these findings. Clinical Significance: SDF‐mediated tooth staining is a serious concern that limits its clinical use. A review of various strategies to overcome this problem will help clinicians enhance its clinical use and patient acceptance.